2019
DOI: 10.1136/bmjopen-2019-029523
|View full text |Cite
|
Sign up to set email alerts
|

Joint impact of dementia and frailty on healthcare utilisation and outcomes: a retrospective cohort study of long-stay home care recipients

Abstract: ObjectivesTo examine the associations between dementia and 1-year health outcomes (urgent hospitalisation, long-term care (LTC) admission, mortality) among long-stay home care recipients and the extent to which these associations vary by clients’ frailty level.DesignA retrospective cohort study using linked clinical and health administrative databases.SettingHome care in Ontario, Canada.ParticipantsLong-stay (≥60 days) care clients (n=153 125) aged ≥50 years assessed between April 2014 and March 2015.Main outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 34 publications
0
8
1
Order By: Relevance
“…Differences observed between dementia populations and those without dementia are likely attributable to differences in dementia severity as well as other important risk factors such as frailty. 27–29 While other studies have demonstrated similar rates of mortality in dementia and non-dementia populations, 11 30 the differences in mortality in our study suggest unmeasured differences in baseline health characteristics beyond age, sex and comorbidities.…”
Section: Discussioncontrasting
confidence: 56%
“…Differences observed between dementia populations and those without dementia are likely attributable to differences in dementia severity as well as other important risk factors such as frailty. 27–29 While other studies have demonstrated similar rates of mortality in dementia and non-dementia populations, 11 30 the differences in mortality in our study suggest unmeasured differences in baseline health characteristics beyond age, sex and comorbidities.…”
Section: Discussioncontrasting
confidence: 56%
“…First, there may be an association between frailty, dementia, and mortality. Frailty, identified as a risk factor for developing dementia [30], has also been associated with increased risk of mortality in people with dementia [31,32]. Furthermore, an autopsy study by Wallace et al [33] reported that people with less frailty were less people who were more frail were more likely to express both neuropathological changes and clinical dementia symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…First, there may be an association between frailty, dementia, and mortality. Frailty, identified as a risk factor for developing dementia [30], has also been associated with increased risk of mortality in people with dementia [31,32]. Furthermore, an autopsy study by Wallace et al [33] reported that people with less frailty were less tor for Alzheimer's dementia.…”
Section: Discussionmentioning
confidence: 99%
“…Dementia or a history of neurological disorders has previously been reported by other authors as being associated with early or late UHR after surgery [8,13,15,19]. Some studies have suggested that patients with dementia have an increased rate of frailty and urgent hospitalization [20][21][22]. It is possible that patients with cognitive or neurological disorders are more likely to decompensate for a chronic condition or represent an acute condition following an initial acute event.…”
Section: Discussionmentioning
confidence: 92%